Surface matters: limitations of CALIPSO V3 aerosol typing in coastal regions - T. Kanitz; A. Ansmann; A. Foth; P. Seifert; U. Wandinger; R. Engelmann; H. Baars; D. Althausen; C. Casiccia; F. Zamorano (Atmospheric Measurement Techniques, 2014)
In the CALIPSO data analysis, surface type (land/ocean) is used to augment the aerosol characterization. However, this surface-dependent aerosol typing prohibits a correct classification of marine aerosol over land that is advected from ocean to land. This might result in a systematic overestimation of the particle extinction coefficient and of the aerosol optical thickness (AOT) of up to a factor of 3.5 over land in coastal areas. We present a long-term comparison of CALIPSO and ground-based lidar observations of the aerosol conditions in the coastal environment of southern South America (Punta Arenas, Chile, 53° S), performed in December 2009–April 2010. Punta Arenas is almost entirely influenced by marine particles throughout the year, indicated by a rather low AOT of 0.02–0.04. However, we found an unexpectedly high fraction of continental aerosol in the aerosol types inferred by means of CALIOP observations and, correspondingly, too high values of particle extinction. Similar features of the CALIOP data analysis are presented for four other coastal areas around the world. Since CALIOP data serve as important input for global climate models, the influence of this systematic error was estimated by means of simplified radiative-transfer calculations.